Iron oxide on carbon‐based supports as efficient catalysts for organic compounds oxidation*. (7th June 2017) - Amini, Mojtaba; Najafpour, Mohammad Mahdi; Salimi, Saeideh; Ramezani, Sakine; Ashouri, Fatemeh; Mahmoudi, Ghodrat
Abstract : For the first time, iron oxide on carbon aerogel, amine functionalized carbon nanotube, black carbon and carboxylic acid functionalized carbon nanotube in the presence of H2 O2 was reported as an efficient and stable catalyst for the selective oxidation of sulfides and alcohols. The catalysts were characterized by scanning electron microscopy, energy‐dispersive spectroscopy, transmission electron microscopy, X‐ray photoelectron spectroscopy, X‐ray diffraction, Fourier transform infrared spectroscopy and atomic absorption spectroscopy. In the next step, catalytic reactivity toward sulfide to sulfoxide and alcohol to aldehyde/ketone oxidation in the presence of H2 O2 was studied and discussed. Abstract : Iron oxide supported on carbon‐based are efficient catalysts for sulfide to sulfoxide oxidation in the presence of H2 O2 .